A rare ovarian tumour, struma ovarii - Inkollu, Sindhura; Kanumury, Vandana; Dasharatha, Murmu; Adusumilli, Padmaja (International Journal of Research in Medical Sciences, 2016)
Struma ovarii is a rare entity, with about 200 reported cases in the medical literature. Struma ovarii is a specialized monodermal teratoma, predominantly composed of mature thyroid tissue. Only 5-8% has functional thyroid tissue. Because of rarity of the tumour, only a few reports with detailed data on thyroid function of the patient have been published. We report here such a case of benign struma ovarii in a 59 year old woman with normal thyroid function. A 59 year old postmenopausal woman was admitted because of an asymptomatic pelvic mass detected on routine pelvic examination. USG revealed a complex right ovarian mass. Patient underwent total hysterectomy with bilateral salphingo-oopherectomy. Histopathological examination revealed struma ovarii without malignancy. Her post-operative course was uneventful. Her thyroid hormone status was in normal range before and after the surgery. We seek to emphasize by this report that, inspite of its rarity, a differential diagnosis of struma ovarii should be included for an ovarian mass regardless of the thyroid hormonal status of the patient, as simple surgery cures the disease in most of the cases even in postmenopausal women without any complications.